Analisis Fungsi Penilaian Kinerja Kepala Sekolah (PKKS) Sebagai Supervisor Pendidikan - Susanti Susanti (ILUMINASI: Journal of Research in Education, 2023)
In order to promote the enhancement of educational quality, this study examines the role that school principal performance evaluations play as educational supervisors. In order to establish ideal standards for school leaders as educational supervisors and to raise teacher professionalism, the goal of this study is to describe the performance appraisal role of educational supervisors. In order to gather information for this work, observation, interviews, and documentation studies were used in conjunction with descriptive qualitative research methods. to do an interactive analysis of the data using Miles and Huberman's model, including data reduction, data display, and conclusion-making. employing the credibility, transferability, dependability, and confirmability tests to determine whether the data is accurate. employing the credibility, transferability, dependability, and confirmability tests to determine whether the data is accurate. According to the study's findings, school principals' performance appraisal activities are very helpful at raising their standards of excellence and professionalism. The principal, who serves as an educational supervisor, is crucial in elevating the professionalism of teachers and the standard of instruction in classrooms. From the foregoing description, it can be inferred that the principle, acting in the capacity of a supervisor, is in charge of the school's education planning program. The principal's own performance, including teacher coaching, also falls under his or her purview as a leader.